Role of criston shear sources in the formation of Chernov-Luders bands - Kashchenko, Mikhail Petrovich; Semenovykh, Anna Gennad’yevna; Nefedov, Aleksey Viktorovich; Kashchenko, Nadezhda Mikhaylovna; Chashchina, Vera Gennadiyevna (Computational Continuum Mechanics, 2021)
Shear bands often appear during plastic deformation. The Chernov-Luders band is an example of a complex multiscale heterogeneous structure containing shear bands. The article is devoted to the analysis of a part of the experimental data on the formation (under tension) of Chernov-Luders band in textured polycrystalline steel samples with fine grain, pre-deformed by rolling. The main attention is focused on the criston mechanism of formation of the observed texture components. The essence of the criston approach, associated with the contact interaction of dislocations at the intersection of slip planes, is briefly described. Information on the observed types of texture is given and a sufficiently detailed analysis of the reconstruction of the mechanism of the appearance of several texture components is carried out taking into account the interaction of the main dislocation slip systems for a body-centered cubic (bcc) lattice. It is shown that some of the real shear directions correspond to the interaction of more than two dislocation slip systems, that is, in fact, there are criston-cristons combinations. A summary table of the results of the analysis of the "composition" of cristons for all texture components is presented, reflecting the fractional contribution of dislocations belonging to interacting slip systems. The analysis has shown that practically all systems of standard slip along the planes of the 110, 112, 123 families play an active role in the formation of cristons and, accordingly, the observed texture. Brief summary comments are provided. In particular, it was noted that, with a sequential criston approach, the issue of non-Schmidian slip variants can be eliminated. The important role of texturing is also noted for the ordering of the intergranular medium and the appearance of macroconcentrators in groups of contacting grains, which, as experience shows, are important in the formation of Chernov-Luders band.